Refractory arterial hypertension: clinical manifestations and controversies - Yuriy I. Karpenko; Saber Garmazi (Journal of Education, Health and Sport, 2015)
Karpenko Yuriy I., Garmazi Saber. Refractory arterial hypertension: clinical manifestations and controversies. Journal of Education, Health and Sport. 2015;5(11):238-244. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33900